IT-Sicherheit: Ökonomisch Planen und Bewerten - Schryen, Guido; Weishäupl, Eva (Managementkompass)

Theory of Knowledge for Literature Reviews: An Epistemological Model, Taxonomy and Empirical Analysis of IS Literature - Schryen, Guido; Wagner, Gerit; Benlian, Alexander (International Conference on Information Systems (ICIS))
Literature reviews play an important role in the development of knowledge. Yet, we observe a lack of theoretical underpinning of and epistemological insights into how literature reviews can contribute to knowledge creation and have actually contributed in the IS discipline. To address these theoretical and empirical research gaps, we suggest a novel epistemological model of literature reviews. This model allows us to align different contributions of literature reviews with their underlying knowledge conversions - thereby building a bridge between the previously largely unconnected fields of literature reviews and epistemology. We evaluate the appropriateness of the model by conducting an empirical analysis of 173 IS literature reviews which were published in 39 pertinent IS journals between 2000 and 2014. Based on this analysis, we derive an epistemological taxonomy of IS literature reviews, which complements previously suggested typologies.
Keywords: Literature review; Research methods/methodology; Theory of knowledge

Resource Planning in Disaster Response - Decision Support Models and Methodologies - Schryen, Guido; Rauchecker, Gerhard; Comes, Martina (Business & Information Systems Engineering (BISE))

Writing qualitative IS literature reviews ? Guidelines for synthesis, interpretation and guidance of research - Schryen, Guido (Communications of the AIS)

Discovering (Hidden) Pathways within the Framework of Design Based Research (DBR) - Developing and "Arena of Innovation" in VET Contexts - Frehe, Petra; Kremer, H.-Hugo (Crossing Boundaries in Vocational Education and Training: Innovative Concepts for the 21st Century. Conference Proceedings.)

Stochastic pumping of a polariton fluid - Assmann, Marc; Bayer, Manfred (PHYSICAL REVIEW A)
We investigate the response of a polariton laser driven slightly off-resonantly using light fields differing from the routinely studied coherent pump sources. The response to driving light fields with thermal and displaced thermal statistics with varying correlation times shows significant differences in the transmitted intensity, its noise, and the position of the nonlinear threshold. We predict that adding more photons on average may actually reduce the transmission through the polariton system.

Electric field effect on optical harmonic generation at the exciton resonances in GaAs - Brunne, D.; Lafrentz, M.; Pavlov, V. V.; Pisarev, R. V.; Rodina, A. V.; Yakovlev, D. R.; Bayer, M. (Physical Review B)
An electric field applied to a semiconductor reduces its crystal symmetry and modifies its electronic structure which is expected to result in changes of the linear and nonlinear response to optical excitation. In GaAs, we observe experimentally strong electric field effects on the optical second (SHG) and third (THG) harmonic generation. The SHG signal for the laser-light k vector parallel to the [001] crystal axis is symmetry forbidden in the electric-dipole approximation, but can be induced by an applied electric field in the vicinity of the 1s exciton energy. Surprisingly, the THG signal, which is allowed in this geometry, is considerably reduced by the electric field. We develop a theory which provides good agreement with the experimental data. In particular, it shows that the optical nonlinearities for the 1s exciton resonance are modified in an electric field by the Stark effect, which mixes the 1s and 2p exciton states of opposite parity. This mixing acts in opposite way on the SHG and THG processes, as it leads to the appearance of forbidden SHG in (001)-oriented GaAs and decreases the crystallographic THG.

Impact of nanomechanical resonances on lasing from electrically pumped quantum dot micropillars - Czerniuk, T.; Tepper, J.; Akimov, A. V.; Unsleber, S.; Schneider, C.; Kamp, M.; Höfling, S.; Yakovlev, D. R.; Bayer, M. (Applied Physics Letters)
We use a picosecond acoustics technique to modulate the laser output of electrically pumped GaAs/AlAs micropillar lasers with InGaAs quantum dots. The modulation of the emission wavelength takes place on the frequencies of the nanomechanical extensional and breathing (radial) modes of the micropillars. The amplitude of the modulation for various nanomechanical modes is different for every micropillar which is explained by a various elastic contact between the micropillar walls and polymer environment.

Photon-Statistics Excitation Spectroscopy of a Quantum-Dot Micropillar Laser - Kazimierczuk, T.; Schmutzler, J.; Aßmann, M.; Schneider, C.; Kamp, M.; Höfling, S.; Bayer, M. (Physical Review Letters)
We introduce photon-statistics excitation spectroscopy and exemplarily apply it to a quantum-dot micropillar laser. Both the intensity and the photon number statistics of the emission from the micropillar show a strong dependence on the photon statistics of the light used for excitation of the sample. The results under coherent and pseudothermal excitation reveal that a description of the laser properties in terms of mean input photon numbers is not sufficient. It is demonstrated that the micropillar acts as a superthermal light source when operated close to its threshold. Possible applications for important spectroscopic techniques are discussed.

Novel mechanisms of optical harmonic generation on excitons in semiconductors - Yakovlev, D. R.; Warkentin, W.; Brunne, D.; Mund, J.; Pavlov, V. V.; Rodina, A. V.; Pisarev, R. V.; Bayer, M. (Nonlinear Optics and Applications IX)

Detection of ultrasonic plate waves using ceramic strip transducers - Claes, Leander; Bause, Fabian; Rautenberg, Jens; Henning, Bernd (Proceedings SENSOR 2015)
Keywords: piezoceramics; strip transducers; plate waveguide; dispersion diagram

Inclusive Beliefs and Self-Efficacy Concerning Inclusive Education Among German Teacher Trainees and Student Teachers - Scheer, David; Scholz, Markus; Rank, Astrid; Donie, Christian (Journal of Cognitive Education and Psychology)

„Alle außer Aaron...“ – Fallbezogene Selbstwirksamkeitserwartungen, Einstellungen und Überzeugungen zukünftiger Lehrkräfte im Kontext Inklusion - Scheer, David; Scholz, Markus; Rank, Astrid; Donie, Christian (Zeitschrift für Heilpädagogik)

Measurement and Analysis of oﬀshore fog occurrences - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the 95th AMS Annual Meeting)

Messtechnisches Prinzip eines neuen Einstrahlungsmessgerätes - Bendfeld, Jörg; Balluff, Stefan; Bermpohl, Wolfgang (Wissenschaftliche Verhandlungen 2015 der Deutschen Physikalischen Gesellschaft)

Performance of MERRA Data in Oﬀshore Wind Energy Applications - Bendfeld, Jörg; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Advanced Integration of Oﬀshore Wind Energy into the Grid System by Power to Gas - Bendfeld, Jörg; Bouyraaman, Yassin; Balluff, Stefan; Krauter, Stefan (Proceedings of the DEWEK 2015)

Comparison of micro inverters based on practical analysis - Sadati, A.M.; Krauter, Stefan; Bendfeld, Jörg (2015 5th International Youth Conference on Energy (IYCE))

Effective large-scale PV integration: Methods to match load profile with actual PV output - Krauter, Stefan (2015 IEEE 42nd Photovoltaic Specialist Conference (PVSC))

Assessment of renewable energy resources in cameroon and special regards on energy supply - Pendieu Kwaye, M.; Bendfeld, Jörg; Anglani, N. (2015 5th International Youth Conference on Energy (IYCE))